2007
DOI: 10.1007/s00198-007-0507-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a fall-prevention program in older people after femoral neck fracture: a one-year follow-up

Abstract: A team applying comprehensive geriatric assessment and rehabilitation, including prevention and treatment of fall-risk factors, reduced inpatient falls and injuries, but no statistically significant effects of the program could be detected after discharge. It seems that fall-prevention must be part of everyday life in fall-prone elderly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 35 publications
0
37
0
Order By: Relevance
“…One of these is a study of whole body vibration in care facilities (Tallon 2013), another is likely to be an additional conference abstract of an already included study (Frohnhofen 2013), and the third is a thesis for which no study publication has been identified (MacRitchie 2001). Five newly published studies were identified in the top-up search and await full assessment (Dever 2016; Hewitt 2014; Raymond 2017; Van der Linden 2017; Wylie 2017). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of these is a study of whole body vibration in care facilities (Tallon 2013), another is likely to be an additional conference abstract of an already included study (Frohnhofen 2013), and the third is a thesis for which no study publication has been identified (MacRitchie 2001). Five newly published studies were identified in the top-up search and await full assessment (Dever 2016; Hewitt 2014; Raymond 2017; Van der Linden 2017; Wylie 2017). …”
Section: Resultsmentioning
confidence: 99%
“…Five newly published studies that were identified in the top-up search in August 2017 await classification (Dever 2016; Hewitt 2014; Raymond 2017; Van der Linden 2017; Wylie 2017). This was a pragmatic decision taken in view of the delay that would have resulted from their likely inclusion and after consideration of the potential impact of these trials on review findings.…”
Section: Discussionmentioning
confidence: 99%
“…However, although there is substantial evidence that fall prevention strategies reduce the number of falls, even in patients with dementia after hip fracture, less evidence is available about their effectiveness in preventing fractures [73][74][75][76][77][78]. Many of the established risk factors for falls have been shown to increase fracture risk as well [79], and this suggests the need for a coordinated programme, with an integrated approach for fall and fracture prevention.…”
Section: Falls Assessmentmentioning
confidence: 98%
“…It should be noted that patients in this series were most likely to have suffered injury outside of normal daytime working hours, and only four falls were witnessed. Inpatient falls can be prevented by nursing high-risk patients in supervised areas, active identification causative factors, and timely assessment of medical issues or post-operative complications [13,16]. After sustaining a FNOF, 100% of patients received a falls assessment which is comparable to a national figure of 94% of patients [1].…”
Section: Day and Time Of Fallmentioning
confidence: 99%